Songlines - Hyde, Joseph, 1969- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1994)
Recording of Joseph Hyde's Songlines. The work is divided into 3 movements: 1. Lost for words, 2. Sound objects, and 3. Marine movement, Movements 2 and 3 are continuous. The "Songlines" are ancient paths crossing the Australian landscape. The landscape in this case is then a long set of texts ranging from Inuit myths to Edgar A. Poe. The synthetic sounds act as if they are traveling and with direction, while also finding new directions and new sounds.